Author Correction: Sex is determined by XX/XY sex chromosomes in Australasian side-necked turtles (Testudines: Chelidae) - Sofa Mazzoleni (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.